FROM PATENT TO PATIENT: LEVERAGING TRIPS FLEXIBILITIES TO OVERCOME IP BARRIERS TO MEDICINES (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the intersection of intellectual property (IP) rights and the right to public health within the framework of the World Trade Organization’s Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). It examines how TRIPS flexibilities, such as compulsory licensing, parallel imports, and exceptions to patent rights, can be effectively used by developing countries to ensure access to essential medicines while complying with international IP obligations. Special attention is given to the 2001 Doha Declaration, which reaffirmed the rights of WTO members to prioritize public health.